Hybrid Multi-Agent Control in Microgrids: Framework, Models and Implementations Based on IEC 61850 - Xiaobo Dou; Xiangjun Quan; Zaijun Wu; Minqiang Hu; Kang Yang; Jian Yuan; Mengmeng Wang (Energies, 2014)
Operation control is a vital and complex issue for microgrids. The objective of this paper is to explore the practical means of applying decentralized control by using a multi agent system in actual microgrids and devices. This paper presents a hierarchical control framework (HCF) consisting of local reaction control (LRC) level, local decision control (LDC) level, horizontal cooperation control (HCC) level and vertical cooperation control (VCC) level to meet different control requirements of a microgrid. Then, a hybrid multi-agent control model (HAM) is proposed to implement HCF, and the properties, functionalities and operating rules of HAM are described. Furthermore, the paper elaborates on the implementation of HAM based on the IEC 61850 Standard, and proposes some new implementation methods, such as extended information models of IEC 61850 with agent communication language and bidirectional interaction mechanism of generic object oriented substation event (GOOSE) communication. A hardware design and software system are proposed and the results of simulation and laboratory tests verify the effectiveness of the proposed strategies, models and implementations.